Effective lasers and enhancement of the radiation-matter interaction via pseudo-Hermitian Hamiltonians - Oliveira Neto, Flávio de (2022)
In this work we propose a method using atom-field effective interactions along with reservoir engineering techniques into laser theory. Our proposal consists of creating generalized operators with which we can re-write the Hamiltonian in the Jaynes-Cummings bilinear form allowing us to build an isomorphism, between the conventional field operators and those of our effective laser, that guarantees the stationary solution in this new basis to be that of the usual theory. Mapping this steady state into the Fock basis we have a new laser state, different from the coherent state, that depends on the choosing of the generalized operator, having no diffusion from cavity losses due to a particular reservoir engineering technique. Moreover, we present a strategy for strengthening the atom-field interaction through a pseudo-Hermitian Jaynes-Cummings Hamiltonian. Apart from the engineering of an effective non-Hermitian Hamiltonian, our method also relies on the accomplishment of short-time measurements on canonically conjugate variables. The resulting fast Rabi oscillations may be used for many quantum optics purposes and specially to shorten the processing time of quantum information.